The Implementation of Authentic Assessment to Evaluate the Students’ Speaking Skill - Sony Junaedi (Journal of English Language Teaching and Islamic Integration, 2019)
The  study  mainly  aims  at  describing  the  implementation  of  authentic assessment to evaluate the students’ speaking skill in the classroom that conducted by lecturer. The objectives of this study were: to describe the authentic assessment implementation,  lecturers’ achievement, their problems, causes of their problems. The  research  design  was  case  study.  Two  English  lecturers  were  chosen  as  the subjects.  The  fourteen  class  observations,  questionnaire  and  interview  were conducted  to  collect  the  data.  The  data  were  analyzed  by  using  Miles  and Huberman’  model  of  analysis.  The  findings  showed  that  basically,  two  English lecturers  have  just  implemented  the  authentic  assessment  but they  have  not  been able  to  implement  it  completely,  properly,  and  smoothly  in  speaking  class  yet. Some  suggestions  can  be  given  in  the  study.  They  should  prepare  the  time allotment properly before preparing, implementing, and scoring students’ skill, look for  many  references,  join  workshop  or  conference  that    relating  to  the authentic assessment in order to understand the ways to design and implement the authentic assessment, score students’ skill and practice them correctly.